MEDICAL PERSONNEL MIGRATION ANALYSIS IN THE CONDITIONS OF HEALTH CARE REFORM IN UKRAINE - Zharlinska, R.G.; Gavriluk, А.О.; Mischuk, А.А.; Вергелес К. М.,; Бабійчук, О.Ю. (World of Medicine and Biology, 2019)
The authors of the article analyze the problems of migration of medical personnel on the basis of analysis and interpretation of statistics and works of leading experts. The priority directions of health care reform in terms of personnel policy have been determined. In particular there аre the creation of proper working conditions and provision of adequate high-paying wages, enhancement of the prestige of the medical profession, improvement of the quality of medical education. The goals of effective personnel management are highlighted, the system of staff motivation to achieve the intended results is analyzed. The authors propose a comprehensive approach to solving the problem of employee’s retention, including through clinical audit.
Keywords: migration of health care workers; employee’s retention; management of medical staff; staff motivation